Cohesive and mixed sediment in the Regional Ocean Modeling System (ROMS v3.6) implemented in the Coupled Ocean–Atmosphere–Wave–Sediment Transport Modeling System (COAWST r1234) - Sherwood, Christopher R.; Aretxabaleta, Alfredo L.; Harris, Courtney K.; Rinehimer, J. Paul; Verney, Romaric; Ferré, Benedicte (Geoscientific Model Development, 2018)
Source at https://doi.org/10.5194/gmd-11-1849-2018 . We describe and demonstrate algorithms for treating cohesive and mixed sediment that have been added to the Regional Ocean Modeling System (ROMS version 3.6), as implemented in the Coupled Ocean–Atmosphere–Wave– Sediment Transport Modeling System (COAWST Subversion repository revision 1234). These include the following: floc dynamics (aggregation and disaggregation in the water column); changes in floc characteristics in the seabed; erosion and deposition of cohesive and mixed (combination of cohesive and non-cohesive) sediment; and biodiffusive mixing of bed sediment. These routines supplement existing noncohesive sediment modules, thereby increasing our ability to model fine-grained and mixed-sediment environments. Additionally, we describe changes to the sediment bed layering scheme that improve the fidelity of the modeled stratigraphic record. Finally, we provide examples of these modules implemented in idealized test cases and a realistic application.